2023
DOI: 10.3389/fimmu.2023.1154699
|View full text |Cite
|
Sign up to set email alerts
|

T cell aging and Alzheimer’s disease

Abstract: The brain has long been considered an immune-privileged organ due to the presence of the blood-brain barrier (BBB). However, recent discoveries have revealed the underestimated role of T cells in the brain through the meningeal lymphatic system. Age is the primary risk factor for Alzheimer’s disease (AD), resulting in marked age-dependent changes in T cells. Manipulating peripheral T cell immune response has been shown to impact AD, but the relationship between T cell aging and AD remains poorly understood. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 102 publications
2
7
0
Order By: Relevance
“…Peripheral immune disorders and peripheral-central immune crosstalk have been investigated for their important roles in the pathogenesis and progression of AD [ 8 ]. Several researchers have demonstrated cytotoxic effects of CD8 + efferent memory CD45RA + (T EMRA ) cells, Th1 and Th17 in CD4 T cells in AD pathology, which is consistent with our study [ 57 , 58 ]. Natural killer (NK) T cells have the ability to rapidly induce cell apoptosis through cytotoxic granules and release of inflammatory factors such as TNF-α, INF-γ.…”
Section: Discussionsupporting
confidence: 93%
“…Peripheral immune disorders and peripheral-central immune crosstalk have been investigated for their important roles in the pathogenesis and progression of AD [ 8 ]. Several researchers have demonstrated cytotoxic effects of CD8 + efferent memory CD45RA + (T EMRA ) cells, Th1 and Th17 in CD4 T cells in AD pathology, which is consistent with our study [ 57 , 58 ]. Natural killer (NK) T cells have the ability to rapidly induce cell apoptosis through cytotoxic granules and release of inflammatory factors such as TNF-α, INF-γ.…”
Section: Discussionsupporting
confidence: 93%
“…Neuronal damage directs CNS tissue regeneration through neuronal stem cell (NSC) and microglial proliferation however, microglial activation can also inhibit CNS regeneration( 97, 108110 ). Aging is known to decrease regenerative NSCs and increase senescent microglia and T cells that secrete pro-inflammatory cytokines( 97, 100, 109, 111113 ). In AD and PD, age-dependent accumulation of senescent NSCs and microglia were associated with a severe proinflammatory state( 100, 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is known to decrease regenerative NSCs and increase senescent microglia and T cells that secrete pro-inflammatory cytokines( 97, 100, 109, 111113 ). In AD and PD, age-dependent accumulation of senescent NSCs and microglia were associated with a severe proinflammatory state( 100, 111 ). Cytokine responses in the CNS of POWV infected 50 week old mice reflect induced senescent cell cytokines (TNFα, IL6, IL-1β) that may contribute to an age-dependent senescence associated secretory phenotype (SASP)( 2, 13, 16, 103, 105, 114 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human patients and mouse models highlighted the potential role and dysfunction of peripheral T cells in AD ( Dai and Shen, 2021 ; Guo et al, 2023 ). Recent studies have shown an increased infiltration of T cells into the brain of old mice and in the plaque-harboring cortex of AD-prone mice ( Mrdjen et al, 2018 ).…”
Section: Meningeal T Cells Behavior During Neuroinflammation and Neur...mentioning
confidence: 99%